Loss of PSMA Expression in Non-neuroendocrine Dedifferentiated Acinar Prostate Cancer. (July 2018) - Bronsert, Peter; Reichel, Kathrin; Ruf, Juri
Abstract : Abstract: The introduction of tracers targeting the prostate-specific membrane antigen (PSMA) has revolutionized PET imaging of acinar prostate adenocarcinoma. In general, an increasing PSMA expression is assumed with increasing dedifferentiation. Whereas loss of PSMA expression has been reported in case of neuroendocrine dedifferentiation, we present a patient with acinar prostate adenocarcinoma with a loss of PSMA expression after chemotherapy on PET/CT and in histological and immunohistochemical analyses. All tissue samples indicated the retention of acinar features but no expression of neuroendocrine markers (NSE, synaptophysin, chromogranin, and CD56), corresponding to nonelevated serum NSE.